2018
DOI: 10.5007/2175-8069.2018v15n34p94
|View full text |Cite
|
Sign up to set email alerts
|

Estrutura de capital: uma revisão bibliográfica das publicações dos periódicos nacionais

Abstract: A estrutura de capital está sendo estudada profundamente desde os trabalhos de Modigliani e Miller (1958 e 1963). Neste contexto, os pesquisadores vêm buscando explicar a utilização das mais diversas estruturas de capital utilizadas e suas aplicações. Assim, esta pesquisa busca identificar como está sendo pesquisada a estrutura de capital em periódicos nacionais. Para tal, foi realizado um levantamento bibliométrico na base Periódicos Capes com os termos estrutura de capital e estrutura da dívida, no título ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 47 publications
0
6
0
2
Order By: Relevance
“…Despite the small number of bibliometric studies in capital structure, it is observed that the researches being developed to fill this gap are recent studies. As the work of Alves and Crisóstomo (2018), Bittencourt and Albuquerque (2018), Nakamura, Jones and Nakamura (2017), Gomes et al (2014), Coelho et al (2013). In Brazil, the publications that carry out bibliometric studies on capital structure are very recent and in smaller volume, compared to the international plane (Alves & Crisóstomo, 2018).…”
Section: Previous Studiesmentioning
confidence: 92%
See 2 more Smart Citations
“…Despite the small number of bibliometric studies in capital structure, it is observed that the researches being developed to fill this gap are recent studies. As the work of Alves and Crisóstomo (2018), Bittencourt and Albuquerque (2018), Nakamura, Jones and Nakamura (2017), Gomes et al (2014), Coelho et al (2013). In Brazil, the publications that carry out bibliometric studies on capital structure are very recent and in smaller volume, compared to the international plane (Alves & Crisóstomo, 2018).…”
Section: Previous Studiesmentioning
confidence: 92%
“…In its turn, Bittencourt and Albuquerque (2018) developed a bibliographical research on capital structure publications in Brazilian journals. The sample consisted of 80 articles, published between 1980 and 2016.…”
Section: Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The determinants of CS portray internal aspects of the firm that can influence financing decisions (Bittencourt & Albuquerque, 2018). The literature points out that understanding the drivers of these decisions remains a challenge for academia and market agents (Bastos et al, 2009;Bernardo et al, 2018).…”
Section: Profitability and Capital Structurementioning
confidence: 99%
“…A construção da terceira categoria "Oportunidade e predominância nas pesquisas" agrupa três artigos teóricos que analisam: o desenvolvimento e potenciais oportunidades de pesquisa acerca da GC (KREUZBERG; VICENTE, 2018); a legitimação do conhecimento em GC no Brasil(MACHADO et al, 2015) e como tem sido pesquisada a estrutura de capital em periódicos nacionais(BITTENCOURT;ALBUQUERQUE, 2018). A seguir, o Quadro 6 apresenta a composição da quarta categoria de análise.REVISTA CIENTÍFICA…”
unclassified